Design and Implementation of an Arduino-Based Body Temperature and Pulse Rate Monitoring System - Bong Siaw Wee; Kong Shuet Fang (International ABEC, 2021)
Health is an important aspect of human existence, and vital indicators such as blood pressure, body temperature, respiration rate, and pulse rate/heart rate are widely known in the medical field. According to the World Health Organization (WHO), 2,200 people die in the United States (U.S.) each day as a result of heart disease. Each year, heart disease and stroke cost about 312.6 billion in health-care expenses. Especially during COVID 19 Pandemic outbreak, rural citizens need a more effective and affordable way for personal healthcare monitoring system before they decide to travel to the nearby medical center for medical assistance. Therefore, the Arduino-Based Body Temperature and Pulse Rate Monitoring System was proposed and developed in this project. The Arduino Software was used to write the programming for this project, which interfaced with the Arduino UNO board. The temperature sensor detects the temperature while the heartbeat sensor counts the pulse rate for a certain interval of time and calculates beats per minute. Both data are delivered to the Arduino UNO for transmission to reception. The results of the measurements will be shown on the Liquid-Crystal Display (LCD) screen. The measured data will be entered into the body temperature and pulse rate app. This App is a platform that presents a graph of the data so that the user can quickly see if the measurements have changed significantly. This app was created utilizing the AppSheet platform's user-friendly features and can be used on a number of platforms, including phones, tablets, and web browsers. The user can retrieve their measurement data anytime and anywhere so that early detection of the heart disease or symptoms of COVID-19. The typical normal temperature of the human body is between 36°C and 37 °C. Low fever is defined as 37.3°C-38 °C, whereas severe fever is defined as 38.1-41 °C. Another function for this innovation project can be used to measure the pulse rate. The normal pulse rate is 60 to 100 beats per minute. People who exceed 100 beats per minute are very dangerous, so they need to refer to the nearest clinic for further medical consultation.